Cancer in the elderly in the Czech Republic. (6th February 2015) - Petera, J.; Dušek, L.; Sirák, I.; Soumarova, R.; Jarkovsky, J.
<x xml:space="preserve">Abstract</x> Population ageing presents a challenge to oncological care due to the particularities of cancer treatment in this population. We evaluate cancer epidemiology, treatment and survival, in the Czech Republic by age groups. Data published by the Czech National Cancer Registry from the years 2006 to 2010 were used for this study. The following cancer types were evaluated: colorectal, pancreatic, head and neck, lung, skin melanoma, breast, gynaecological, prostate, kidney and stomach cancers. The following data were recorded and analysed: crude incidence by 5‐year age group; dynamics of crude incidence rates in the age group ≥70 years; disease stage; percentage of patients treated by surgery, radiotherapy and chemotherapy; and age standardised 1‐year mortality and 5‐year relative survival according to age group. Patients over age 70 accounted for 41% and 46%, respectively, of the cancer incidence and mortality of the whole population. Anticancer therapies are significantly less common in patients over age 70 (P < 0.050), with the exception of skin melanoma. Survival was markedly worse in older patients (P < 0.050) when radical treatment modalities were significantly underused (P < 0.050). In the Czech Republic, the crude cancer incidence in seniors is increasing. In general, elderly patients are undertreated, with worse treatment results compared with younger patients.